Astragalus membranaceus Extract (AME) Enhances Growth, Digestive Enzymes, Antioxidant Capacity, and Immunity of Pangasianodon hypophthalmus Juveniles - Hany M. R. Abdel-Latif; Hamada A. Ahmed; Mustafa Shukry; Md Reaz Chaklader; Rasha M. Saleh; Mohamed A. Khallaf (Fishes, 2022)
The present study evaluated the impacts of powdered Astragalus membranaceus extract (AME) on the growth, physiological responses, and serum immunity of Pangasianodon hypophthalmus juveniles. Four test diets were formulated to include varying AME levels as 0.0 (control), 1.5 (AME1.5), 3.0 (AME3.0), and 4.5 (AME4.5) g/kg. Fish weighing approximately 11.50 g were stocked into four triplicate groups and hand-fed on the test diets three times daily for two months. At 60 days post-feeding, the growth performance, including weight gain and the specific growth rate, was increased quadratically (R2 > 0.90) with increasing AME inclusion levels. An improvement in the feed intake and feed conversion ratio were also noticed in groups fed at different AME levels. The whole-body and amino acid composition were unaffected by the test diets. A significant quadratic trend in the digestive enzymes (lipase, α-amylase, and protease) was found along with increasing AME inclusion levels. Liver enzymes associated with liver functions were improved by AME dietary inclusion levels. Meanwhile, the blood urea nitrogen, uric acid, and creatinine values were unaffected by AME dietary inclusion. On the other hand, serum immunity (lysozyme and total Igs) was elevated with a significant quadratic trend along with increasing AME dietary inclusion levels. Liver MDA levels decreased with increasing AME levels. Liver CAT, GPx, and SOD enzyme activities demonstrated a significant increasing trend along with dietary AME inclusion. The aforementioned effects of dietary AME on P. hypophthalmus health underpinned the potentiality of AME to be used as a phyto-additive to improve the functionality of aquafeed.